Evaluation of Four Plant Species for Phytoremediation of Cadmium-and Copper-Contaminated Soil - Ahmadpour, Parisa (2011)
Application of weeds and leafy wild vegetables for phytoremediation of cadmium (Cd) - and copper (Cu)-contaminated soils is well documented; however, limited research has been conducted on forest trees. Cd and Cu are known as the most dangerous pollutants, particularly at higher concentrations. This thesis reports two studies on the phytoremediation of Cd- and Cu-contaminated soils using four forest species, namely Jatropha curcas, Acacia mangium, Dyera costulata, and Hopea odorata. Randomized completely block design (RCBD) with four replications was used in a factorial arrangement in each study. The aim of this study was to assess the phytoremediation potential of the four tested species for Cd- and Cu-contaminated soil and then to recommend the most suitable species for phytoremediation of the soil contaminated with Cd and Cu. In the first study, cadmium chloride (CdCl2.2•5H2O) was used as a source of Cd. The growth media were prepared using soil mixed with different levels of Cd. The different levels of growth media (soil + different levels of Cd) were Cd0 (control soil), Cd1 (soil + 25 mg kg-1 Cd), Cd2 (soil + 50 mg kg-1 Cd), Cd3 (soil + 75 mg kg-1 Cd), Cd4 (soil + 100 mg kg-1 Cd), and Cd5 (soil + 150 mg kg-1 Cd). For the second study, copper sulphate (CuSO4•5H2O) was used as a source of Cu. The different levels of growth media were Cu0 (control soil), Cu1 (soil + 50 mg kg-1 Cu), Cu2 (soil + 100 mg kg-1 Cu), Cu3 (soil + 200 mg kg-1 Cu), Cu4 (soil + 300 mg kg-1 Cu), and Cu5 (soil + 400 mg kg-1 Cu). The pots were filled with growth media, and the seedlings of the four plant species were transplanted after one month. The parameters monitored and analyzed were soil physico-chemical properties, growth variables (basal stem diameter, height and number of leaves), plant dry biomass (dried biomass of leaves, stems, and roots), and heavy metal concentrations both in the growth media and in the plant parts (leaves, stems, and roots). The results of the first study revealed that higher levels of Cd significantly (p≤0.05) influenced both growth variables and plant dry biomass. The growth variables of the four tested species decreased with increase in the level of Cd. Increasing Cd levels also disaffect production of dry biomass. There was significant difference (p≤0.05) in total Cd concentration (Cd concentration in leaves + stems + roots) among plant species grown under different Cd levels. Among seedlings exposed to Cd5, J. curcas showed the highest total Cd concentration (1125.68 mg kg-1). Cd removal efficiency (RE), bioconcentration factor (BCF), and translocation factor (TF) were significantly different (p≤0.05) among plant species grown under different Cd levels. Among seedlings exposed to Cd5, J. curcas exhibited the highest Cd removal (0.64%). The BCFs of Cd in plant species were >1 under various Cd levels, except in control media. Plant species grown in control media showed the high TFs (>1), whereas the plant species grown in the media treated with different Cd levels exhibited low TFs (<1). Among plant species exposed to Cd5, the highest BCF (7.17) and TF (0.61) were recorded in J. curcas and H. odorata, respectively. As for the second experiment, the growth variables and dry biomass of the four tested species were significantly influenced (p≤0.05) by different Cu levels. Higher Cu levels significantly decreased (p≤0.05) the growth performance and the production of dry biomass. Total Cu concentration in tested species increased significantly (p≤0.05) with increase in the Cu level. Among seedlings exposed to Cu5, J. curcas showed the highest total Cu concentration (665.04 mg kg-1). The Cu removal efficiency, BCF, and TF were significantly different (p≤0.05) among plant species grown under different Cu levels. J. curcas attained the highest Cu removals within each level of Cu. The BCFs of Cu were >1 within each level of Cu and in control media. Plant species grown in the control media showed TFs >1, whereas plant species grown in the media treated with various levels of Cu exhibited very small TFs (<1). Among plant species exposed to Cu5, the highest RE, BCF, and TF (0.23%, 1.76, and 0.33, respectively) were found in J. curcas. In general, the highest total Cd and Cu concentration and the maximum Cd and Cu removal efficiency among plant species were observed in J. curcas. In addition, most parts of Cd and Cu accumulated in roots of the four tested species in both experiments. As a conclusion, J. curcas was the most effective species in both studies for phytoremediation of Cd- and Cu-contaminated soils through phytostabilization.